2022
DOI: 10.1111/jocn.16441
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting triage competence among emergency room nurses: A cross‐sectional study

Abstract: Aims and Objectives:The purpose of this study was to examine work-related stress, nurse-physician collaboration and clinical reasoning competence to identify the factors that affected the triage competence of emergency room nurses.Background: A quick and accurate treatment plan for patients is first determined by a triage nurse. Triage competence is an indispensable requirement for emergency room nurses.Design: A cross-sectional design was adopted. Methods:The participants comprised 156 emergency room nurses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…45 This effect is further explained by the finding that nurse-physician collaboration is negatively correlated with nursing outcomes, such as triage competence and clinical reasoning competence, among nurses working in the emergency department. 44 Moreover, evidence in the literature supports a serial mediation effect of POS and nurse-nurse collaboration on the relationship between role overload and MNC (H 5 ). 19,[46][47][48] Nurses recognize that the lack of organizational support is an obstacle to successful teamwork in difficult situations with heavy responsibilities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…45 This effect is further explained by the finding that nurse-physician collaboration is negatively correlated with nursing outcomes, such as triage competence and clinical reasoning competence, among nurses working in the emergency department. 44 Moreover, evidence in the literature supports a serial mediation effect of POS and nurse-nurse collaboration on the relationship between role overload and MNC (H 5 ). 19,[46][47][48] Nurses recognize that the lack of organizational support is an obstacle to successful teamwork in difficult situations with heavy responsibilities.…”
Section: Discussionmentioning
confidence: 96%
“…43 In addition, these findings of sequential mediation effects are supported by the empirical findings in prior studies, linear associations between organizational support, interprofessional collaboration or teamwork, and nursing outcomes. 25,28,44,45 Higher perceived support in the organizational context, such as authentic leadership and structural empowerment, results in a higher perceived level of interprofessional collaboration. 28 Consequently, interprofessional collaboration has partial indirect effects on the relationships between the nursing work environment and nursing outcomes, quality of care, and adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating the performance of an AI model, it is important to compare it with a gold standard. Using the judgments of nurses and doctors as the gold standard for classi cation raises concerns that bias among raters may occur because the subjective opinion of the rater affects the classi cation result [22][23][24]. In this study, only one supplemented the vulnerability of the gold standard by adding the results of specialists, and all others were compared based on the judgment results of nurses and doctors, which may vary depending on the practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…However, the manual input method for patient triage by nurses can be hindered by factors such as the pressure to deal with many patients, the chaotic environment within the emergency department, and the presence of waiting ambulances, which can disrupt the decision-making process [21]. It has been observed that nurses' capacity for triage, including their training, knowledge, clinical experience, and communication skills, can in uence its effectiveness [22,23]. Moreover, accurate assessment and triage are crucial for ensuring patient safety and saving lives.…”
Section: Introductionmentioning
confidence: 99%